THE ASSESSMENT METHODOLOGIES PTELR, ADRI AND CAE – THREE METHODOLOGIES FOR COORDINATING THE EFFORTS TO IMPROVE THE ORGANIZATIONAL PROCESSES TO ACHIEVE EXCELLENCE - Cristina Raluca POPESCU; Gheorghe N. POPESCU (Challenges of the Knowledge Society)
In the paper “The Assessment Methodologies PTELR, ADRI and CAE – Three Methodologies for Coordinating the Efforts to Improve the Organizational Processes to Achieve Excellence” the authors present the basic features of the assessment methodologies PTELR, ADRI and CAE that are designed to coordinate the efforts to improve the organizational processes in order to achieve excellence. In the first part of the paper (the introduction of the paper), the authors present the general background concerning the performance of management business processes and the importance of achieving excellence and furthermore correctly assessing/evaluating it. Aspects such as quality, quality control, quality assurance, performance and excellence are brought into discussion in the context generated by globalization, new technologies and new business models. Moreover, aspects regarding the methods employed to ensure the quality, maintaining it and continuous improvements, as well as total quality management, are also main pillars of this current research. In the content of the paper (the assessment methodologies PTELR, ADRI and CAE – as methodologies for coordinating the efforts to improve the organizational processes to achieve excellence), the authors describe the characteristics of the assessment methodologies PTELR, ADRI and CAE from a theoretical point of view.